DIFFERENCES IN MOTOR AND FUNCTIONAL SKILLS OF BOYS IN A THIRD GRADE OF ELEMENTARY SCHOOL - Dževad Džibrić; Alen Kapidžić; Tarik Huremović; Fatmir Pireva (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Based on the sample of 128 boys in a third grade of Elementary school, age of 8 (± 6 months), the differences between motor and functional skills in initial and final measuring were being determined. Entire sample was divided in three sub samples. Sub sample of 42 respondents who regularly participate in physical and health education, monitored and taught by professors of physical education, attending two classes per week (first experimental group). Sub sample of 45 respondents who regularly participate in physical and health education, monitored and taught by physical education professors, attending two classes per week plus one additional class (second experimental group). Sub sample of 41 respondents who regularly participate in physical and health education, monitored and taught by physical education professors attending two classes weekly (control group). Experimental program was implemented during first half of a school year. After conducted experimental procedure, according to obtained results we determined statistically significant difference between control and experimental groups, as well as between the two experimental groups. According to above mentioned we can conclude that experimental program implemented in this research contributed in favor of differences of experimental groups.